The miRNome of canine invasive urothelial carcinoma - Varvil, Mara S.; Bailey, Taylor; Dhawan, Deepika; Knapp, Deborah W.; Ramos-Vara, José A.; Santos, Andrea P. dos (Frontiers in Veterinary Science, 2022)
Urothelial carcinoma (UC) comprises up to 2% of all naturally occurring neoplasia in dogs and can be challenging to diagnose. MicroRNAs (miRNA) have been reported to be dysregulated in numerous diseases, including neoplasia. MiRNA expression has been evaluated in human UC, but there is limited information regarding the miRNA transcriptome of UC in dogs. Our study aimed to evaluate differential miRNA expression in bladder tissue collected from normal canine urothelium and canine invasive UC (iUC) to elucidate the dysregulated pathways in canine UC. Next-Generation RNA sequencing (RNA-Seq) was performed for dogs with UC (n=29) and normal canine urothelium (n=4). Raw RNA data were subjected to normalization, and pairwise comparison was performed using EdgeR with Benjamini-Hochberg FDR multiple testing correction (p<0.05; >2 fold change) comparing tissue samples of normal urothelium to canine iUC samples. Principal component analysis and hierarchical cluster analysis were performed. MiRNA of FFPE tissue samples of separate iUC (n=5) and normal urothelium (n=5) were used to evaluate five miRNAs using RT-qPCR. Pathway analysis was performed utilizing miRwalk, STRING database, and Metascape utilizing KEGG pathways and GO terms databases. Twenty-eight miRNAs were differentially expressed (DE) by RNA-Seq. RT-qPCR confirmed four miRNA are significantly downregulated in UC compared to healthy urothelial samples (miR-105a, miR-143, miR-181a, and miR-214). Principal component analysis and hierarchical cluster analysis showed separation between miRNA in iUC and the control group. The DE miRNAs are most often associated with gene silencing by miRNA, miRNAs in cancer, and miRNAs involved in DNA damage responses. Proteins involved include HRAS, KRAS, ARAF, RAF1, MAPK1, MAP2K1, MAPK3, FGFR3, EGFR, HBEGF, RASSF1, E2F2, E2F3, ERBB2, SRC, MMP1, and UP3KA. The presence of differential expression of miRNA in canine iUC compared to normal canine urothelial tissue indicates that these markers should be further evaluated for their potential role as diagnostic and therapeutic targets.